Development of Teaching Arabic as a Foreign Language in Learning - Hafiz Azhar Nasution; Chairunnisya Sitompul; Dika Sabilla; Darma Subianto (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
Language is an important communication tool that humans use in everyday life. In psycholinguistic studies, language is seen from a psychological aspect that studies how humans communicate and understand language. A second language is a language learned after the mother tongue, and is often considered a foreign language. Many people think Arabic is difficult to learn, but actually each language has different levels of difficulty and ease depending on its characteristics, such as morphology, phonology, syntax and semantic systems. This research uses a qualitative method with a descriptive approach through observation, interviews and documentation. This research aims to understand the history of the development of Arabic in Sumatra, which is supported by the role of mosques and Islamic boarding schools as centers for Arabic language education. Apart from that, this research also highlights the relationship between Arabic and cultural perspectives as well as Islamic religious views towards Arabic. Arabic has a long history in Sumatra, with mosques and Islamic boarding schools as learning centers that teach Arabic letters, verses from the Koran, and rules of worship. From a cultural perspective, Arabic acts as a universal means of communication and connection to Islamic culture. In the Islamic religion, Arabic is considered the unified language of Muslims and is used in worship rituals. Arabic is also recognized as an international language by the UN, showing its importance in the development of Islamic science and Islamic civilization.